HUMAN CAPITAL MANAGEMENT FROM PSYCHOANALYTIC PERSPECTIVE - Jay Nathan; Kaliyeva S.; Baisalova B. (Academic Journal of Physical and Chemical Sciences, 2020)
The article presents a psychoanalytic interpretation of organizational hierarchy in the aspect of human capital, considering the positive and negative consequences for all organization members. Its aim is to present the psychoanalytic understanding of the capital which is constituted by organization members. It is them who decides about the effects of the operations of an organization, both its successes and failures. This article attempts at describing the psychological mechanisms which determine the complex phenomenon called ‘human capital’ of an organization. The concept of ‘human capital’ has been confronted with one of the key attributes of an organization, that is the hierarchy of the organization’s structure. The article presents a psychoanalytic interpretation of organizational hierarchy in the aspect of human capital, considering the positive and negative consequences for all organization members.